(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Network theory investigates the operation of diverse sectors such as commerce, electrical and electronic circuits, and computer networks, among other things. It has operation that is the graphical display of data in numerous areas of activity. Network theory can graph symmetrical and asymmetrical connections between discrete items. In the computer science sector, for example, network theory is defined as a graphical illustration of systems having nodes and edges. The notion of network theory was discussed in this article, as well as its use in numerous fields, as well as its limits and benefits. In this post, we’ll look at how network theory is used in electrical engineering to address problems. The numbers of current and voltage component in a circuit is first determined using network theory, and then the circuit is simplified using network theory. By applying complex network analysis, this article presents a concept on complex network analysis (CNA) as well as brief information on micro grids in electric distributions system. Network theory is learning of electrical network that can aid in the future, such as improving the network stability of a major power station, increasing grid resilience, and protecting power stations from blackouts. The study of network theory is demonstrated in this article using MATLAB software.